Experimental Study on Functionally Graded Steel Fibre Reinforced Preplaced Aggregate Concrete - Prasad. K, Ram; G, Murali.; Kathirve, Parthiban; M K, Haridharan; K, Karthikeyan. (International Journal of Engineering and Technology, 2018)
This study examines compressive strength of this functionally graded steel fibre reinforced concrete (FGFRPAC). A five mixes were prepared and tested in the present study. The first series of FGFRPAC were prepared and reinforced in three layers of 3%, 1.5% and 3% with crimped, hooked end. The second series were reinforced with 2.5% steel fibre equally in all the three layers. The average amount of fibre used in FGFRPAC specimen was 2.5% which is similar to the fibre dosage used in the second series were the fibres are equally spread in all the three layers. The gathered results revealed that employing FGFRPAC leads to more enhancement in compressive strength than conventional steel fibre reinforced concrete.